Optimal Regimens and Cutoff Evaluation of Tildipirosin Against Pasteurella multocida - Lei, Zhixin; Liu, Qianying; Qi, Yi; Yang, Bing; Khaliq, Haseeb; Xiong, Jincheng; Moku, Gopi Krishna; Ahmed, Saeed; Li, Kun; Zhang, Hui; Zhang, Wenqiu; Cao, Jiyue; et al. (Frontiers in Pharmacology, 2018)
Pasteurella Multocida (PM) can invade the body upper respiratory tract and causes death and high morbidity. Tildipirosin, a new 16-membered ring macrolide antimicrobial, has been recommended for the treatment of the respiratory diseases. The objective of this research was to improve the dose regimes of tildipirosin to PM for reducing the macrolides resistance development with pharmacokinetic/pharmacodynamic (PK/PD) modeling approach, and establish an alternate cut-off for tildipirosin against PM. Single dose (4 mg/kg body weight) of tildipirosin was administered via intramuscular (i.m) and intravenous injection (i.v) to the pigs. The minimum inhibitory concentration (MIC) values of clinical isolates (112) were measured in the range of 0.0625 to 32 μg/ml, and the MIC50 and MIC90 values were 0.5 and 2 μg/ml, respectively. The MIC of the selected PM04 was 2 and 0.5 μg/ml in the TSB and serum, respectively. The main pharmacokinetics (PK) parameters including AUC24h, AUC, T1/2, Tmax, Cmax, CLb and MRTlast were calculated to be 7.10, 7.94 μg*h/ml, 24.02, NA h, NA μg/ml, 0.46 L/h*kg, 8.06 hand 3.94, 6.79 μg*h/ml, 44.04, 0.25 h, 0.98 μg/ml, 0.43 L/h*kg, 22.85 h after i.v and i.m induction, respectively. Moreover, the bioavailability of i.m route was 85.5% and the binding of tildipirosin to serum protein was 78%. The parameters AUC24h/MIC in serum for bacteriostatic, bactericidal and elimination activities were calculated as 18.91, 29.13 and 34.03 h based on the inhibitory sigmoid Emax modeling. According to the Monte Carlo simulation, the optimum doses for bacteriostatic, bactericidal and elimination activities were 6.10, 9.41, and 10.96 mg/kg for 50% target and 7.86, 12.17 and 14.57 mg/kg for 90% target, respectively. The epidemiological cut-off was calculated to be 4 μg/ml which could cover 95% wild-type clinical isolates distribution. The PK-PD cutoff was analyzed to be 0.25 μg/ml in vitro for tildipirosin against PM based on the Monte Carlo simulation. Compared with these two cut-off values, the finial susceptible breakpoint was defined as 4 μg/ml. The current data presented provides the optimal regimens (12.17 mg/kg) and susceptible breakpoint (4 μg/ml) for clinical use, but these predicted data should be validated in the clinical practice.